Microsoft Excel Program Training at the Dumai Petroleum Vocational School, Riau Province - Fitrianti Fitrianti*; Adi Novriansyah; Roza Mildawati; Sri Hartati Dewi; Firdaus Agus (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Education at the Vocational High School (SMK) level is an important alternative for students to develop their skills and be ready to face competition in an increasingly competitive job market. SMK graduates have technical skills and are ready to enter work sectors related to procedures and routines. In Riau Province, the upstream oil and gas industry provides opportunities for SMK graduates to participate in this sector. SMK Migas in Duri City and Dumai City were established to prepare students for positive contributions to the oil and gas industry around the region. The development of technology, especially in the field of information technology, encourages the industry to apply the technology in every aspect of its operations. Modernization and digitalization also affect the oil and gas industry sector, which includes exploration and exploitation activities. The oil and gas industry requires reliable human resources (HR), given the density of capital and technology in this sector. However, companies tend to look for experienced workers, so SMK graduates need to have skills that can be directly used in the oil and gas industry. The transition to an increasingly advanced technological era requires SMK graduates to have the ability to adapt to technology, especially in the use of computers as a means of work and learning. Behave=adaptive Being able to operate the Microsoft Office program package is an important requirement for every individual who uses a computer, either in the form of a personal computer (PC) or laptop. Laptops are also the main device for freelance engineers in conducting engineering analysis from simple to complex.